2000
DOI: 10.1046/j.1439-037x.2000.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Konkurrenz und Ertragsvorteile in Gemengen aus Erbsen (Pisum sativum L.) und Hafer (Avena sativa L.)

Abstract: Competition and yield advantage in mixtures of pea (Pisum sativum L.) and oats (Avena sativa L.) In field trials on a fertile fluvisol in 1995 and 1996 near Göttingen, Germany, pea (Pisum sativum; cv. Messire/conventional leafed, cv. Profi/semileafless) and oats (Avena sativa; cv. Alf) were grown as sole crops and in substitutive mixtures. The sole crops were established at 80 pea seeds m−2 and 300 oat seeds m−2. The mixtures consisted of 67 % (pea) and 33 % (oats) of the monoculture densities, respectively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…Beyond this stage, the grower has to scarify either for the protein or for fodder yield. The findings of this study are similar to the findings of Al-Masri (1998) and Rauber et al (2000). Assefa and Ledin (2001) also reported that DM forage yield of pure vetch; pure oat and mixture were 4.3, 7.6 and 7.3 t ha -1 respectively.…”
Section: Dry Matter Yield (T Ha -1 )supporting
confidence: 91%
“…Beyond this stage, the grower has to scarify either for the protein or for fodder yield. The findings of this study are similar to the findings of Al-Masri (1998) and Rauber et al (2000). Assefa and Ledin (2001) also reported that DM forage yield of pure vetch; pure oat and mixture were 4.3, 7.6 and 7.3 t ha -1 respectively.…”
Section: Dry Matter Yield (T Ha -1 )supporting
confidence: 91%
“…Grains were weighed and samples taken to determine the dry matter content after they had been dried at 105°C for 48 h. For further agronomic and experimental details see Kimpel‐Freund et al. (1998), Kimpel‐Freund (1999) and Rauber et al. (2000).…”
Section: Methodsmentioning
confidence: 99%
“…Plants were harvested by hand (2´1 m 2 per plot) when pea and oat were at the dry seed stage. Grains were weighed and samples taken to determine the dry matter content after they had been dried at 105°C for 48 h. For further agronomic and experimental details see Kimpel-Freund et al (1998), Kimpel-Freund (1999) and Rauber et al (2000). Data on symbiotic nitrogen ®xation of Messire, Pro®, Bohatyr and Juno in pure stands and mixtures were taken from Schmidtke (1997) who used the d 15 N technique (Shearer and Kohl 1986).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies with pea and a cereal species in mixture have been undertaken using the replacement series design where the total relative seed frequency of the mixture is equal to the relative seed frequency of the sole crops (Tofinga and Snaydon, 1992;Jensen 1996aJensen , 1996bRauber et al 2000Rauber et al , 2001. On the other hand, an increasing number of authors have found that advantages can be gained by growing mixtures of legumes and nonlegumes when grown in total densities higher than those of the sole crops in comparison to replacement series mixtures.…”
Section: Introductionmentioning
confidence: 99%